A cross-sectional study for estimation of associations between education level and osteoporosis in a Chinese men sample. Issue 1 (December 2015) - Yu, Cai-Xia; Zhang, Xiu-Zhen; Zhang, Keqin; Tang, Zihui
Abstract Background The main aim of this study was to evaluate the association between education level and osteoporosis (OP) in general Chinese Men. Methods We conducted a large-scale, community-based, cross-sectional study to investigate the association by using self-report questionnaire to assess education levels. The data of 1092 men were available for analysis in this study. Multiple regression models controlling for confounding factors to include education level were performed to explore the relationship between education level and OP. Results Positive correlations between education level and T-score of quantitative bone ultrasound (QUS-T score) were reported (β  = 0.108, P value < 0.001). Multiple regression analysis indicated that the education level was independently and significantly associated with OP (P  < 0.1 for all models). The men with lower education level had a higher prevalence of OP. Conclusion The education level was independently and significantly associated with OP. The prevalence of OP was more frequent in Chinese men with lower education level. Trial registration ClinicalTrials.gov Identifier:NCT02451397 ; date of registration: 05/28/2015).